2009
DOI: 10.1021/je800615s
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Enthalpies of Amino Acids and Glycine Peptides from Water to Aqueous Solutions of Sugar Alcohol at 298.15 K

Abstract: Enthalpies of solution of glycine, l-alanine, l-serine, l-threonine, diglycine, and triglycine in aqueous solutions of d-sorbitol, d-mannitol, and xylitol have been measured by calorimetry at 298.15 K. These data have been used to calculate the transfer enthalpies of the amino acids and glycine peptides from water to aqueous solutions of sugar alcohol. It has been observed that all the values of the transfer enthalpies are negative and decrease with an increase of the concentration of sugar alcohol in the aque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…(3)-(5) corresponded to the standard enthalpy of Gly-Gly dissolution in pure water, its values coinciding well with the earlier determined reference values: Δ sol Н 0 (Gly-Gly) 11.56±0.07 [11], 11.67 [12], and 11.81±0.0.03 [13]. The enthalpy pair interaction parameters h xy were calculated as h xy = a 1 /2 [14].…”
Section: Mezhevoi Badelin 818supporting
confidence: 82%
“…(3)-(5) corresponded to the standard enthalpy of Gly-Gly dissolution in pure water, its values coinciding well with the earlier determined reference values: Δ sol Н 0 (Gly-Gly) 11.56±0.07 [11], 11.67 [12], and 11.81±0.0.03 [13]. The enthalpy pair interaction parameters h xy were calculated as h xy = a 1 /2 [14].…”
Section: Mezhevoi Badelin 818supporting
confidence: 82%
“…Ionic liquids are assumed to be the appropriate medium for studying protein stability . Thermodynamic studies on amino acids as a function of concentration and temperature in the presence of various additives have been performed to understand solute–solvent interactions. Ionic liquids have been utilized in aqueous biphasic systems consisting of amino acids, to study the protein stability in the presence of ionic liquids that has attracted the attention of different researchers toward their physicochemical properties. Thermodynamic variables like temperature and pressure affect proteins in aqueous medium and play a key role in establishing a complete interpretation of the physical immutability .…”
Section: Introductionmentioning
confidence: 99%
“…Here, by applying Pierotti's approach, we calculated thermodynamic parameters of solvation for xylitol in water and in aqueous amino acids at 298.15 K. Literature survey indicates that no work has been reported on xylitol–amino acid interactions using SPT. However, studies have been reported on xylitol–amino acid interactions using volumetric, calorimetric, solubility and tensiometric methods. These considerations led us to undertake the present study.…”
Section: Introductionmentioning
confidence: 99%